3D Transient heat transfer analysis and flow visualization study in diverging microchannel for instability mitigated two-phase flow: A numerical study. (October 2020) - Alugoju, Uday Kumar; Dubey, Satish Kumar; Javed, Arshad
Highlights: 3D numerical simulation of flow boiling in diverging microchannel heat sink. The effect of varying divergence angle, width, and wall contact angle has been studied. Volume of fluid (VOF) along with phase change model is used for the numerical study. Varying nucleation time and bubble patterns was observed for different channels. Flow reversal was observed in the channel with divergence angle 0.38°. Abstract: This paper presents a 3D conjugate numerical simulation of the diverging microchannel heat sink, which is performed using the Volume of Fluid (VOF) model coupled with the phase change model. The modeling approach and simulation results are validated with standard correlations and published experimental results. The model is used to analyze the flow boiling and transient heat transfer mechanism through simulation of bubble nucleation, bubble growth pattern, pressure, temperature, and vapor quality variations. Moreover, local and transient Heat Transfer Coefficient (HTC) is calculated and then correlated with the simulated bubble dynamics. Herein, simulations are performed on the expanding microchannel with a varying outlet to inlet width ratio for uniform heat flux 150 kW/m 2 at two different mass fluxes 240 kg/m 2 s and 710 kg/m 2 s. Further, to understand the effect of wall contact angle, simulations are performed for two different values of wall contact angle of 140° and 65°. The results indicate that the channels with low divergence angle (θ) and low outlet to inlet width ratio (δ) have low nucleation time. Rapid bubble growth and elongated flow due to channel confinement were also observed. Higher values of the heat transfer coefficient are observed in the microchannels with small hydraulic diameter, and as the diameter is increased, a reduction in the HTC values is observed. The transient heat transfer coefficient fluctuation in the channel with time has been studied along with the corresponding flow pattern. Due to the smaller wall contact angle, the bubble separation rate from the wall is low, thereby creating localized hotspots. A comparative study between straight channel and diverging channel has showed that diverging microchannels have a better performance in terms of instability mitigated flow boiling. This study has considerable relevance in electronic chip cooling using expanding microchannel with instability mitigated two-phase flow.